Cardiovascular disease outcomes in relation to 25-hydroxyvitamin D and its seasonal variation: Results from the BiomarCaRE consortium - Viktor Oskarsson; Veikko Salomaa; Pekka Jousilahti; Luigi Palmieri; Chiara Donfrancesco; Susana Sans; Licia Iacoviello; Simona Costanzo; Marco M. Ferrario; Giancarlo Cesana; Barbara Thorand; Annette Peters; et al. (PLoS ONE, 2025)
Background It has been hypothesized but seldom tested that the winter excess in cardiovascular disease (CVD) is related to hypovitaminosis D. The present study examined the association between CVD and (i) seasonality of 25-hydroxyvitamin D (25[OH]D) and (ii) individual 25(OH)D concentrations. Methods and findings Harmonized 25(OH)D data were obtained from the Biomarkers for Cardiovascular Risk Assessment in Europe (BiomarCaRE) project, including 79,570 participants examined between 1984 and 2010. One 25(OH)D measurement was available per participant. Primary endpoints were CVD incidence (coronary heart disease or stroke; n = 6006) and CVD mortality (n = 2985). To study (i), Poisson regression-derived rate ratios were compared according to two-month categories, ordered by baseline 25(OH)D concentrations. To study (ii), Cox regression-derived hazard ratios were compared according to quarters of baseline 25(OH)D concentrations. With respect to (i), despite a median 25(OH)D concentration ratio of 1:1.79, the trough months of 25(OH)D in March and April had a similar CVD incidence as the peak months of 25(OH)D in August and September (rate ratio: 1.07, 95% CI: 0.98–1.17). CVD mortality was slightly higher in the trough months compared to the peak months (rate ratio: 1.27, 95% CI: 1.12–1.44) but not compared to the other months (despite median 25[OH]D concentration ratios up to 1:1.62; p ≥ 0.077). The CVD mortality peak in January preceded the 25(OH)D trough, not adhering to the temporality criterion of Bradford Hill. With respect to (ii), compared to the lowest quarter, the highest quarter of 25(OH)D was associated with lower CVD incidence (hazard ratio: 0.82, 95% CI: 0.76–0.89) and CVD mortality (hazard ratio: 0.64, 95% CI: 0.57–0.72). Conclusion The present study does not support the hypothesis that seasonal increases in CVD are driven by short-term reductions in 25(OH)D. As in most observational studies, higher 25(OH)D concentrations were inversely associated with CVD.